Identifying three-dimensional palmprints with Modified Four-Patch Local Binary Pattern (MFPLBP) - Musab T.S. Al-Kaltakchi; Manhal Ahmad Saleh Al-Hussein; Raid Rafi Omar Al-Nima (International Journal of Electronics and Telecommunications)
Palmprint biometrics is the best method of identifying an individual with a unique palmprint for every person. The present paper formulates a new methodology towards the identification of 3D palmprints using the Modified Four- Patch Local Binary Pattern (MFPLBP). It improves upon the conventional Four-Patch Local Binary Pattern (FPLBP) by integrating the adaptive weight with the improved texture extraction. Both approaches are created to support the intricate surface information of 3D palmprints. The MFPLBP can exactly capture local variations and is noise and illumination invariant. There are extensive experiments done in this paper and establish that MFPLBP outperforms traditional LBP methods and other stateof- the-art methods in recognition rates. The experiments establish that MFPLBP is a efficient and effective method of making use of 3D palmprints in real-world biometric verification.